Green kiwifruit: effects on plasma lipids and APOE interactions - Gammon CS; Kruger R; Minihane AM; Conlon CA; von Hurst PR; Stonehouse W (Massey University)
Background Diet is a crucial element in the reduction of risk of cardiovascular disease (CVD). Furthermore, response to dietary change may be influenced by genotype. Kiwifruit are a good source of several dietary components shown to improve dyslipidaemia and lower CVD incidence such as soluble fibre and some vitamins and phytochemicals. Objective To investigate the effect of consuming two green kiwifruit daily in conjunction with a healthy diet on plasma lipids and examine response according to apolipoprotein E (APOE) genotype in hypercholesterolaemic men. Design Eighty-five hypercholesterolaemic men (low-density lipoprotein cholesterol (LDL-C) >3.0 mmol/L and triglycerides (TG) <3 mmol/L) completed an eight week randomised controlled cross-over study, after undergoing a four week healthy diet phase. The study consisted of two 4-week treatment sequences of 2 green kiwifruit/day plus healthy diet (intervention) or healthy diet alone (control). Fasting blood samples were taken at baseline, 4 and 8 weeks for the measurement of plasma lipids (total cholesterol (TC), LDL-C, TG, high-density lipoprotein cholesterol (HDL-C)), serum apolipoproteins A1 and B (apoA1 and apoB). Outcomes After the kiwifruit intervention plasma HDL-C concentrations were significantly higher (mean difference 0.04 [95% CI: 0.01, 0.07] mmol/L [P=0.004]) and the TC/HDL ratio was significantly lower (0.15 [-0.24, -0.05] mmol/L [P=0.002]), compared to control. In carriers of APOE4 allele TG concentrations were significantly lower (0.18 [-0.34, -0.02] mmol/L [P=0.03]) after the kiwifruit intervention compared to control. There were no significant differences between the two treatments for plasma TC, TG, LDL-C and serum apoA1 or apoB. Conclusion The small but significant increase in HDL-C and decrease in TC/HDL ratio and TG (in APOE4 carriers) suggests that the regular inclusion of green kiwifruit as part of a healthy diet may be beneficial in improving the lipid profiles of men with high cholesterol. Source of Funding: ZESPRI® International Trial No: ACTRN12610000213044
Keywords: Kiwifruit; APOE; Lipids; Cardiovascular disease